Precarious land tenure and public policy in Jujuy, Argentina. An analysis of the links between province, nation and indigenous peoples - Borghini, Natalia (2010)
The objective of this work is to analyze public policies and national and provincial legislation, oriented to guaranteeing territorial rights of native communities in Jujuy. We will focus on the management of a program to regularize lands in the province. Our hypothesis is that this novel policy comes from a change in the vision of these actors, nationwide, and not from  pressure put on by civil society. The results of this investigation allow us to sustain the foregoing, as well as to understand the role and transformations of the provincial State and the indigenous communities in the process.